Anti-seizure effects of JNJ-54175446 in the intra-amygdala kainic acid model of drug-resistant temporal lobe epilepsy in mice - Mamad, Omar; Heiland, Mona; Lindner, Andreas U.; Hill, Thomas D. M.; Ronroy, Ronan M.; Rentrup, Kilian; Sanz-Rodriguez, Amaya; Langa, Elena; Heller, Janosch P.; Moreno, Oscar; Llop, Jordi; Bhattacharya, Anindya; et al. (Frontiers in Pharmacology, 2024)
There remains a need for new drug targets for treatment-resistant temporal lobe epilepsy. The ATP-gated P2X7 receptor coordinates neuroinflammatory responses to tissue injury. Previous studies in mice reported that the P2X7 receptor antagonist JNJ-47965567 suppressed spontaneous seizures in the intraamygdala kainic acid model of epilepsy and reduced attendant gliosis in the hippocampus. The drug-resistance profile of this model is not fully characterised, however, and newer P2X7 receptor antagonists with superior pharmacokinetic profiles have recently entered clinical trials. Using telemetry-based continuous EEG recordings in mice, we demonstrate that spontaneous recurrent seizures in the intraamygdala kainic acid model are refractory to the common anti-seizure medicine levetiracetam. In contrast, once-daily dosing of JNJ-54175446 (30 mg/kg, intraperitoneal) resulted in a significant reduction in spontaneous recurrent seizures which lasted several days after the end of drug administration. Using a combination of immunohistochemistry and ex vivo radiotracer assay, we find that JNJ-54175446-treated mice at the end of recordings display a reduction in astrogliosis and altered microglia process morphology within the ipsilateral CA3 subfield of the hippocampus, but no difference in P2X7 receptor surface expression. The present study extends the characterisation of the drug-resistance profile of the intraamygdala kainic acid model in mice and provides further evidence that targeting the P2X7 receptor may have therapeutic applications in the treatment of temporal lobe epilepsy.